Climate Shocks, Migration, and Labor Markets: A Gender Analysis from West Africa - Nelly Elmallakh; Quentin Wodon (Global Labor Organization (GLO), 2021)
This paper investigates the effects of shocks, predominantly climate shocks, on labor market outcomes in the West African Economic and Monetary Union (WAEMU). We focus on migration ows within the WAEMU countries to disentangle the differential effects of shocks on migrants and non-migrants. Our analysis combines survey data from Ivory Coast|as the main migrant receiving country|and from all the other 7 migrant sending countries of the WAEMU. Using an OLS fixed effects model, our results show that migration in the WAEMU is associated with a decline in female labor participation, as it is primarily motivated by marriage. However, we find an increase in female labor force participation and a narrowing of the gender gap in migrant households that are negatively affected by shocks. Our findings relate to the literature on the impact of shocks on the labor division between women and men and show that shocks may disrupt long-standing gender roles. The results are robust to accounting for the double selection into shocks and migration using a Propensity Score Matching technique that allows for a within comparison between treated and untreated units.
Keywords: F22; J21; J43; J61; Q54; 330; shocks; migration; climate; employment; labor market; women; West Africa